Probing lepton number violation and Majorana nature of neutrinos at the LHC - K. S. Babu; Rahool K. Barman; Dorival Gonçalves; Ahmed Ismail (Journal of High Energy Physics, 2024)
Abstract Observation of lepton number (L) violation by two units at colliders would provide evidence for the Majorana nature of neutrinos. We study signals of L-violation in the context of two popular models of neutrino masses, the type-II seesaw model and the Zee model, wherein small neutrino masses arise at the tree-level and one-loop level, respectively. We focus on L-violation signals at the LHC arising through the process pp → ℓ ± ℓ ′± + jets within these frameworks. We obtain sensitivity to L-violation in the type-II seesaw model for triplet scalar masses up to 700 GeV and in the Zee model for charged scalar masses up to 4.8 TeV at the high-luminosity LHC with an integrated luminosity of 3 ab−1.